A rate-1 2 × 2 Space-Time code without any constellation extension for TH-UWB communication systems with PPM - Abou-Rjeily, Chadi (2017)
In this paper, we propose for the first time a 2 × 2 space-time (ST) block code that can be applied with pulse position modulation (PPM) without introducing any constellation extension. This encoding scheme is adapted to low cost carrierless time-hopping ultra-wideband (TH-UWB) systems where information must be conveyed only by the time delay of the modulated signal that has a very low duty cycle. The proposed scheme permits to achieve full transmit diversity with M-ary PPM constellations for all values of M. Moreover, it permits to overcome the additional phase rotations or amplitude amplifications that are introduced by all the known ST codes such as the Alamouti code (S.M. Alamouti, 1998), the rate-1 codes proposed in B.A. Sethuraman et al. (2003), (A. J. Hammons and H. El Gamal, 2000) for PSK and the diversity schemes proposed in L. Yang and G.B. Giannakis (2004) for TH-UWB systems with PAM or PPM.